The adipokine chemerin amplifies electrical field-stimulated contraction in the isolated rat superior mesenteric artery - Darios, Emma S.; Winner, Brittany M.; Charvat, Trevor; Krasinksi, Antoni; Punna, Sreenivas; Watts, Stephanie W. (American journal of physiology. Heart and circulatory physiology, 2016)
The adipokine chemerin causes arterial contraction and is implicated in blood pressure regulation, especially in obese subjects with elevated levels of circulating chemerin. Because chemerin is expressed in the perivascular adipose tissue (PVAT) that surrounds the sympathetic innervation of the blood vessel, we tested the hypothesis that chemerin (endogenous and exogenous) amplifies the sympathetic nervous system in mediating electrical field-stimulated (EFS) contraction. The superior mesenteric artery, with or without PVAT and with endothelium and sympathetic nerve intact, was mounted into isolated tissue baths and used for isometric contraction and stimulation. Immunohistochemistry validated a robust expression of chemerin in the PVAT surrounding the superior mesenteric artery. EFS (0.3–20 Hz) caused a frequency-dependent contraction in isolated arteries that was reduced by the chemerin receptor ChemR23 antagonist CCX832 alone (100 nM; with, but not without, PVAT), but not by the inactive congener CCX826 (100 nM). Exogenous chemerin-9 (1 μM)-amplified EFS-induced contraction in arteries (with and without PVAT) was blocked by CCX832 and the α-adrenergic receptor antagonist prazosin. CCX832 did not directly inhibit, nor did chemerin directly amplify, norepinephrine-induced contraction. Whole mount immunohistochemical experiments support colocalization of ChemR23 with the sympathetic nerve marker tyrosine hydroxylase in superior mesenteric PVAT and, to a lesser extent, in arteries and veins. These studies support the idea that exogenous chemerin modifies sympathetic nerve-mediated contraction through ChemR23 and that ChemR23 may be endogenously activated. This is significant because of the well-appreciated role of the sympathetic nervous system in blood pressure control.